Kajian Minat Membaca Siswa di Kelas 3 SD Negeri 34 Parit Madura - Sidehri, Sidehri; Afryaningsih, Yunika; Fatmawati, Risdiana Andika (Lembaga Intelektual Muda Maluku, 2025)
This study aims to describe the reading interest of third-grade students at SDN 34 Parit Madura and the factors that influence it. The research uses a descriptive qualitative approach with a Guttman scale-based questionnaire, supplemented by observations and interviews. The data are analyzed descriptively using the National ALIBACA Index classification. The results show that the overall reading interest of third-grade students at SDN 34 Parit Madura falls into the moderate category with an average of 54.76%. The reading attention aspect is categorized as high with 76.20%, reflecting students’ strong enthusiasm and interest in reading activities, although concentration still needs improvement. The reading preference and number of books owned aspects are in the moderate category, each with 52.38%. Meanwhile, the reading time aspect is categorized as low with 38.10%, since most students do not yet have a consistent daily reading routine. These findings suggest that students already possess potential reading interest, but it has not yet developed into a strong habit. This study recommends the implementation of more effective literacy strategies through the provision of diverse reading materials, the habituation of reading both at home and at school, and collaboration between teachers and parents in fostering a literacy culture